THE EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE ON TUAN RONDAHAIM HOSPITAL PAMATANG RAYA - Panjaitan, Hadi; Zhou, Weihuan; Saragih, Jopinus; Florenta Butar-Butar, Diana; Setiawan, Ben (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
In this study there are two variables are variables X (Discipline) and Y (Performance). This study aims to examine and analyze the influence of compensation for employee work at Tuan Rondahaim Hospital Pamatang Raya. Based on the incidental sample method, the total sample in this study was 62 respondents. In this study using primary data obtained from the distribution of questionnaires. The number of questionnaires distributed as many as 62 copies and which can be returned and processed as many as 62 copies. The method of analysis used in this study is simple linear regression analysis and hypothesis testing (t-test). Amount of t-counts (8.382) > of the amounth of t-tables (1.99897) then Ha accepted. Based on these results it can be concluded that the compensation has a positive and significant effect on employees'